Myeloperoxidase as a marker of vascular damage - Ming R. Xu, Anjali L. Sharma (Open Journal of Physicians and Surgeons, 2024)
Myeloperoxidase, an enzyme primarily found in neutrophils and monocytes, has emerged as a marker of vascular damage and inflammation. Elevated levels of myeloperoxidase have been associated with oxidative stress, endothelial dysfunction, and the development of atherosclerosis and cardiovascular diseases. As a key player in the generation of reactive oxygen species, myeloperoxidase contributes to the oxidative modification of lipoproteins, promoting the formation of atherosclerotic plaques. Moreover, myeloperoxidase has been implicated in the activation of inflammatory pathways within the vascular wall, further exacerbating vascular damage and promoting a proatherogenic environment. Measuring myeloperoxidase levels in blood or tissues can provide valuable insights into the extent of vascular damage and inflammation. Elevated myeloperoxidase levels have been correlated with poor cardiovascular outcomes and increased risk of adverse events in individuals with various vascular conditions. By understanding the role of myeloperoxidase as a marker of vascular damage, clinicians and researchers can potentially utilize this enzyme as a diagnostic and prognostic tool in assessing cardiovascular risk, monitoring disease progression, and developing targeted therapies to mitigate vascular pathology.